Cuticular hydrocarbons as a basis for chemosensory self‐referencing in crickets: a potentially universal mechanism facilitating polyandry in insects. (21st December 2012) - Weddle, Carie B.; Steiger, Sandra; Hamaker, Christopher G.; Ower, Geoffrey D.; Mitchell, Christopher; Sakaluk, Scott K.; Hunt, John; Grether, Greg
Abstract Females of many species obtain benefits by mating polyandrously, and often prefer novel males over previous mates. However, how do females recognise previous mates, particularly in the face of cognitive constraints? Female crickets appear to have evolved a simple but effective solution: females imbue males with their own cuticular hydrocarbons (CHCs) at mating and utilise chemosensory self‐referencing to recognise recent mates. Female CHC profiles exhibited significant additive genetic variation, demonstrating that genetically unique chemical cues are available to support chemosensory self‐referencing. CHC profiles of males became more similar to those of females after mating, indicating physical transfer of CHCs between individuals during copulation. Experimental perfuming of males with female CHCs resulted in a female aversion to males bearing chemical cues similar to their own. Chemosensory self‐referencing, therefore, could be a widespread mechanism by which females increase the diversity of their mating partners.